2001
DOI: 10.1007/pl00008565
|View full text |Cite
|
Sign up to set email alerts
|

Parasite and vertebrate host genetic heterogeneity determine the outcome of infection by Schistosoma mansoni

Abstract: Intraspecific variation in Schistosoma mansoni infection and modulation of its expression by vertebrate host genetics was studied by evaluation of some biological parameters of the infection in BALB/c and C57BL/6 mice infected with one Brazilian (BH) and two Venezuelan (YT and SM) laboratory strains of the parasite. Mice infected with 60 cercariae of each parasite strain were euthanized at 5, 6, 8, and 12 weeks. Parameters recorded included the number of adult worms recovered by portal perfusion (infectivity);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 16 publications
1
26
4
Order By: Relevance
“…Thus, it has been well documented that the mean prepatent period is five-six weeks post infection (Kassim et al 1979). Strains that have been maintained for a long period of time under laboratory conditions had a smaller prepatent period compared to newly isolated strains (Fallon et al 1997, Incani et al 2001, Yoshioka et al 2002.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been well documented that the mean prepatent period is five-six weeks post infection (Kassim et al 1979). Strains that have been maintained for a long period of time under laboratory conditions had a smaller prepatent period compared to newly isolated strains (Fallon et al 1997, Incani et al 2001, Yoshioka et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that Schistosoma mansoni geographical strains exhibit variability related to infectivity, prepatent period, fecal egg excretion, liver or intestinal egg counts and altered response to schistosomicidal drugs in rodent models (Kassim et al 1979, Coelho et al 1997, Incani et al 2001, Yoshioka et al 2002, Bonesso-Sabadini & Dias 2002. However, little attention has been paid to the biological characteristics of sympatric human and murine strains.…”
mentioning
confidence: 99%
“…The host genotype seems to influence schistosome fecundity (Jones et al 1989) and the loss of worms from the portal system of infected mice (Cheever et al 1994). Incani et al (2001) reported that the strain of the host appeared to influence the susceptibility to infection, the fecundity, and the percentage of eggs distributed in the liver and in the intestine during the chronic stage of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the laboratory mouse has been the experimental model of choice to study pathogenesis of infection, including innate and acquired host defense mechanisms. Inbred mouse strains differ significantly in their degree of susceptibility to infection with various human bacterial (eg, Mycobacterium tuberculosis, 15,16 Salmonella enterica, 17 Streptococcus pyogenes, 18 Streptococcus pneumoniae 19 ), fungal (eg, Histoplasma capsulatum, 20 Aspergillus fumigatus 21 ), protozoan (eg, Leishmania major, 22 Plasmodium berghei, 23 Plasmodium chabaudi 24 ), helminthic (eg, Schistosoma mansoni 25,26 ) as well as viral (eg, respiratory syncytial virus 27,28 ) pathogens. This attribute has been exploited to identify novel loci influencing resistance/susceptibility to infection and to provide new insight on host mechanisms involved in response to those pathogens that ultimately affect the onset, progression, and outcome of the infection.…”
mentioning
confidence: 99%